2003
DOI: 10.1091/mbc.e03-01-0040
|View full text |Cite
|
Sign up to set email alerts
|

The Role of mVps18p in Clustering, Fusion, and Intracellular Localization of Late Endocytic Organelles

Abstract: Delivery of endocytosed macromolecules to mammalian cell lysosomes occurs by direct fusion of late endosomes with lysosomes, resulting in the formation of hybrid organelles from which lysosomes are reformed. The molecular mechanisms of this fusion are analogous to those of homotypic vacuole fusion in Saccharomyces cerevisiae. We report herein the major roles of the mammalian homolog of yeast Vps18p (mVps18p), a member of the homotypic fusion and vacuole protein sorting complex. When overexpressed, mVps18p caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
95
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 62 publications
10
95
0
Order By: Relevance
“…27 Although we are not able to detect significant amounts of MYO1C on LAMP1-positive organelles under steady-state conditions, previous reports show that overexpression of VPS18, a component of the mammalian HOPS complex, causes clustering of late endosomes and/or lysosomes in actin-rich areas and recruitment of MYO1C to these compartments. 28 These results suggest that MYO1C may indeed be able to associate with endolysosomes, however, under steady-state conditions the recruitment of a limited number of MYO1C motors from the cytosolic pool might be transient and therefore difficult to detect by standard immunofluorescence microscopy.…”
Section: Discussionmentioning
confidence: 85%
“…27 Although we are not able to detect significant amounts of MYO1C on LAMP1-positive organelles under steady-state conditions, previous reports show that overexpression of VPS18, a component of the mammalian HOPS complex, causes clustering of late endosomes and/or lysosomes in actin-rich areas and recruitment of MYO1C to these compartments. 28 These results suggest that MYO1C may indeed be able to associate with endolysosomes, however, under steady-state conditions the recruitment of a limited number of MYO1C motors from the cytosolic pool might be transient and therefore difficult to detect by standard immunofluorescence microscopy.…”
Section: Discussionmentioning
confidence: 85%
“…Overexpression of mammalian class C VPS protein homologs (e.g., VPS18 and VPS39) in human cells causes perinuclear clustering of late endosomes and lysosomes [25][26][27] . This is consistent with a role for these class C complex components in the recruitment of these membrane-bound organelles for the fusion events required for endo-or exocytosis and secretion.…”
Section: Nature Geneticsmentioning
confidence: 99%
“…For example, the HOPS complex proteins (Vps11p, Vps16p, Vps18p, and Vps33p) regulate membrane fusion events necessary for lysosomal delivery within yeast (Rieder and Emr, 1997;Peterson and Emr, 2001), Drosophila melanogaster (Sevrioukov et al, 1999;Sriram et al, 2003), and mammalian (Poupon et al, 2003;Richardson et al, 2004) endosomal systems. Similarly, the proteins composing the AP-3 complex control the formation of transport vesicles for lysosomal cargo in each of these species (Odorizzi et al, 1998;Bonifacino and Traub, 2003;Luzio et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the HOPS complex proteins (Vps11p, Vps16p, Vps18p, and Vps33p) regulate membrane fusion events necessary for lysosomal delivery within yeast (Rieder and Emr, 1997;Peterson and Emr, 2001), Drosophila melanogaster (Sevrioukov et al, 1999;Sriram et al, 2003), and mammalian (Poupon et al, 2003;Richardson et al, 2004) endosomal systems. Similarly, the proteins composing the AP-3 complex control the formation of transport vesicles for lysosomal cargo in each of these species (Odorizzi et al, 1998;Bonifacino and Traub, 2003;Luzio et al, 2003).Although the yeast vacuole has proven to be a useful model for studying basic features of lysosomes, studies in Drosophila, mammals, and Caenorhabditis elegans have identified genes necessary for the formation of lysosomes that are not conserved in yeast (Lloyd et al, 1998;Spritz, 1999;Marks and Seabra, 2001;Piper and Luzio, 2004;Treusch et al, 2004). For example, the Hook family of proteins are present in Drosophila (Kramer and Phistry, 1996), C. elegans (Malone et al, 2003), and mammals but not in yeast (Walenta et al, 2001).…”
mentioning
confidence: 99%